Peran Mu‘askar al-Lughah dalam Meningkatkan Keterampilan Berbicara Bahasa Arab / The Role of Mu'askar al-Lughah In Improving Arabic Speaking Skills - Basmala Basmala; Mujahid Mujahid; Rahmat R; Hamzah Hamzah; Basri Mahmud (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2023)
This is study aims to describe the role of language camps in improving Arabic speaking skills for KIBAR IAI DDI Polewali Mandar students in the 2021/2022 academic year. This type of research is qualitative research that builds meaning based on field data. This qualitative research procedure produces descriptive data in the from of written or spoken words from people and observable behavior. Data was collected by conducting observations, in-depth interviews, and documentation. Data analysis was carried out by reducing data, presenting data, and verifying data. Testing the validity of the data used is triangulation, member check, increasing persistence. The results of this study are 1) the role of language camps in improving Arabic speaking skills for KIBAR IAI DDI Polewali Mandar students for the 2021/2022 academic year is to form an Arabic language environment. 2) The inhibiting factors is the lack of ability of the committee in directing students who have not been able to speak Arabic well. Supporting factors include the Arabic environment throughout the day and mastery of Arabic vocabulary. 3) The language camp program has a positive impact, namely being able to speak Arabic in daily activities.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan peran muaskar al-lugah dalam meningkatkan keterampilan berbicara bahasa Arab pada pelajar KIBAR IAI DDI Polewali Mandar tahun akademik 2021/2022. Jenis penelitian ini adalah penelitian kualitatif yang membangun makna berdasarkan data lapangan. Prosedur penelitian kualitatif ini menghasilkan data deskriptif berupa kata-kata tertulis atau lisan dari orang-orang dan perilaku yang diamati. Pengumpulan data dilakukan dengan mengadakan observasi, wawancara mendalam, dan dokumentasi. Analisis data dilakukan dengan cara mereduksi data, penyajian data, dan verifikasi data. Pengujian keabsahan data yang digunakan adalah triangulasi, member check, dan meningkatkan ketekunan. Hasil penelitian ini yaitu 1) peran muaskar al-lugah dalam meningkatkan keterampilan berbicara bahasa Arab pada pelajar KIBAR IAI DDI Polewali Mandar tahun akademik 2021/2022 ialah membentuk lingkungan bahasa Arab. 2) Adapun faktor penghambat yaitu kurangnya kemampuan panitia dalam mengarahkan pelajar yang belum mampu berbahasa Arab dengan baik. Faktor pendukungnya meliputi lingkungan bahasa Arab sepanjang hari dan penguasaan kosakata bahasa Arab. 3) Program muaskar al-lugah memberikan dampak positif yaitu mampu berbicara menggunakan bahasa Arab dalam aktivitas sehari-hari.